FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PERUSAHAAN MANUFAKTUR YANG TELAH GO PUBLIK DI BEI TAHUN 2009-2011 (Students' Journal of Economic and Management, 2014)
The aim this research is to analyze and investigate the factors that influence of capital structure manufacturing company which go public in Indonesian Stock Exchange. Specifically this research proposed fadlowing research question does frim size, business risk, and profitability factors influence to capital structure in manufacturing company. This research population is manufacturing company which go public in Indonesian Stock Exchange in the year 2009 until year 2011. Intake of sample conducted whith technique of purposive sampling and find 101 company fulfilling criterion as sample Analysis technique implemented does multiple regression analysis models.The result of this research show that variable influence to capital structure in manufacturing company is frim size dan profitability variable while business risk variable do not influence to capital structure. Research findings indicated that the more tangibility of assets firm influence meaningless, the more collateral assets to get external sources such as debt, meanwhile the frim size in fluencing capital structure policy is because the bigger the frim size that reflected from tangibility assets the bigger capital structure, in this case the debt of that frim so it can be expleained that capital structure have some influences to the capital structure. Key words : Capital Structure, Size, Business Risk, Profitability.